Asymmetric information on non-cognitive skills in the Indian labor market: An experiment using an online job portal - Yamauchi, Futoshi; Nomura, Shinsaku; Imaizumi, Saori; Areias, Ana C; Chowdhury, Afra R (International Food Policy Research Institute, 2018)
This paper examines the impact of non-cognitive (socio-emotional) skills on job market outcomes using a randomized control trial implemented in an online job portal in India. Job seekers who registered in the portal were asked to take a Big Five type personality test and, for a random sub-sample of the test takers, the results were displayed to potential employers. Outcomes are measured by whether a potential employer shortlists a seeker by opening (unlocking) his/her application and background information. The results show that the treatment group for whom test results were shown generally enjoyed a higher probability of unlock. That is, employers are more interested in those for whom they can see personality test results. Such a relationship was not seen in the pre-test period, which confirms that the above results are unlikely to be spurious. We also found a significant impact among organized, calm, imaginative and/or quiet applicants (no effect was detected among easy-going, sensitive, realistic and/or out-going applicants), which seems to display employers’ preferences.